LC-MS study analyzing tongue coating metabolites in intra-oral halitosis patients - Dr Wenjie Yang (Elsevier, 2023)
Aim or Purpose: The coating of tongue is an important source of intra-oral halitosis, analyzing the metabolites can provide powerful insights into the metabolic mechanism of intra-oral halitosis patients. Materials and Methods: Intra-oral halitosis caused by oral diseases was excluded in this study to reduce the impact of common oral diseases on research results. Subjects who meet the inclusion criteria were chosen, and their halitosis was evaluated using the organoleptic score and two instruments, which is Halimeter® and OralChroma™. Patients with a complaint of halitosis and a confirmed diagnosis of halitosis were assigned to the halitosis group, while healthy individuals without a complaint of halitosis and regular oral examination were assigned to the control group. Samples of tongue coating were collected. The metabolites of tongue coating were detected using liquid chromatography-mass spectrometry, the difference of tongue coating metabolites between intra-oral halitosis patients and healthy individuals were compared. Results: There were 21 people in the halitosis group and 20 people in the control group. There are differences in the tongue coating metabolites between intra-oral halitosis patients and healthy individuals. On the basis of variable importance on projection values (VIP>1) and P values (P<0.05), 204 different metabolites were identified, primarily organic acids and derivatives, organic heterocyclic compounds and lipids and lipid-like molecules. Conclusions: There are significant differences in the metabolites of tongue coating between intra-oral halitosis patients and healthy individuals. The differential metabolites with diagnostic value may be used as diagnostic markers of intra-oral halitosis.